Kyselina kojová a jej deriváty ako potenciálne liecivá - Uher, M; Chalabala, M; Cizmárik, J (Ceska a Slovenska farmacie, 2000)
The review paper studies kojic acid, a secondary metabolite of fibrous fungi, as a carrier chemical structure of potential pharmaceuticals. The examined preparative procedures, physico-chemical and biologic properties, and especially the antifungal and antileukemic effects of the parent kojic acid indicate that novel potential drugs can be developed on its basis.
Keywords: Structure-Activity Relationship; molekulární struktura; vztahy mezi strukturou a aktivitou; Antifungal Agents; Molecular Structure; pyrony; Pyrones; antifungální látky; Mycotoxins; Leukemia; Animals; lidé; leukemie; Humans; zvířata; mykotoxiny